Educação ambiental crítica e sustentabilidade em portos na amazônia: o programa de educação ambiental da Companhia Docas do Pará - NUNES, Alexandre Rodrigues da Silva (Universidade Federal do Pará, 2021)
This work dissertational has the theme Environmental Education and port as its object the Environmental Education Program of the Dock Company of Pará presented as objective the descriptive analysis of this program in Miramar Petrochemical Terminal relating to the National Environmental Education (Law No. 9795 / 99) and other relevant laws. It questioned the effectiveness of environmental education as a public policy. In order to meet environmental laws do Pará Dock Company (CDP) in partnership with the Federal University of Pará (UFPA) through the Study Group on Education, Culture and Environment (GEAM) in 2005 deploys the Education Program Environment at the Port of Vila do Conde, Port of Santarem, in 2007 in Miramar Petrochemical Terminal program that reaches both the officials of the ports and terminals and to the neighborhoods surrounding communities through various activities (courses, workshops and lectures) related to Environmental Education. The methodology used was documentary research from the descriptive analysis of the Activity Reports of the Environmental Education Program in Petrochemical Terminal Miramar. Used as the theoretical understanding of the object to the assumptions of historical and dialectical materialism related to the concept of Environmental Education critical, emancipatory, and transformative popular, since we are faced with a scenario of environmental unsustainability through policies of unbridled exploitation of natural resources and threat to biodiversity, biomes, ecosystems and have repercussions on increasing social and environmental inequalities. Thus, we conclude that the Environmental Education Program of the Dock Company of Pará should be understood as an element of legitimacy and effectiveness of the National Environmental Education, this policy is the result of social demands, but that is an answer and reveal the face of reformist and conservative the state and the capitalist system in its actions. Therefore, despite advances in the debates and discussions that envisioned in the descriptive analysis of the program, it needs to emphasize the need to overcome the reality of global socio-environmental crisis in their practice to enable effective transformations relating the local to global.